Economic evaluations of RSV preventive strategies: a systematic review of cost-effectiveness and modeling approaches - Zhu, Bingde; Lu, Yuqiong; Zhou, Yang; Li, Weixiao; Wu, Yuhang; Bao, Yujin; Lu, Yun (Frontiers in Public Health, 2025)
BackgroundRespiratory syncytial virus (RSV) causes significant morbidity and mortality worldwide, particularly in high-risk groups. Despite the availability of preventive interventions, it is crucial to evaluate the economic benefits of these interventions.MethodsThis systematic review assessed the cost-effectiveness and model structures of RSV prevention strategies, including vaccines and monoclonal antibodies, by analyzing studies published up to March 2025.ResultsA total of 39 studies were included, comprising one cost–benefit analysis (CBA) and 38 cost–effectiveness analyses (CEAs), utilizing six different types of economic models. The incremental cost-effectiveness ratio (ICER) among the older adult population varied from 5,342 to 385,829 per quality-adjusted life year (QALY). One study demonstrated superior cost-effectiveness of a long-acting monoclonal antibody (LAMA) compared to a short-acting monoclonal antibody, with both being more economically favorable than maternal vaccines for pregnant women and neonates. The most sensitive variables were intervention efficacy, price, and immunity duration.ConclusionMost RSV vaccines and monoclonal antibody interventions demonstrate cost-effectiveness in specific populations and settings. However, cost-effectiveness is highly influenced by intervention price, efficacy, duration, populations, and administration time.Systematic review registrationThe protocol for this study has been registered with PROSPERO under the registration number CRD42024524720.